CLINICAL CHARACTERISTICS OF THE TYPES OF DAILY BLOOD PRESSURE PROFILES IN PATIENTS WITH ARTERIAL HYPERTENSION DEPENDING ON THE SELECTED ABPM INDEX - Petrenko, O. V.; MartynenkoО. V.; Yabluchansky, M. I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2016)
The frequency characteristics of the clinical signs of arterial hypertension (AH) according to the daily profile type of systolic (SBP), diastolic (DBP) and pulse (PP) blood pressure were studied. The data showed a significant difference in the frequency of occurrence of AH clinical signs, depending on the type of daily profile of SBP, DBP, and PP. It was concluded that in patients with AH determination only SBP daily profile of is not enough, it’s necessary to take into account the types of DBP and PP daily profiles also. AH 1 degree was more common among SBP-overdippers, DBP-night-peakers and PP-dippers, and AH 2 degree – among SBP-nondippers, DBP-dippers and PP-night-peakers, which as a whole accounted for more than half of all cases. AH 3 degree met more common only among the SBP-night-peakers, where it accounted for 1/3 of the observations. The highest incidence of AH stage I was noted in the group of DBP-overdippers. Stage II prevailed in all groups of patients, accounting for half and more of all cases, with minor differences between the groups. Stage III was more common among PP-overdippers. Patients with chronic HF prevailed and accounted for more than half of all cases in the vast majority of patients groups, with the highest incidence among SBP- and DBP-night-peakers and DBP-nondippers. I stage of HF significantly prevailed in all groups, accounting for half and more of all cases. Stage IIA was more common among SBP-night-peakers and DBP-nondippers, III stage – among SAD-nondippers, DBP-dippers and PP-night-peakers and didn’t exceed 1/10 of all cases. Chronic HF FC I met with the greatest frequency in groups of SBP- and DBP-night-peakers, II FC – in the group of DBP-nondippers, III FC - among DBP-dippers. Different frequency ratio of AH clinical signs dependently of SBP, DBP and PP daily profiles requires that in AH diagnosis, prognosis and monitoring of treatment all their multitude should be takeт into consideration, but not only SBP diurnal profiles alone.